Application of phosphorescent oxygen sensors in in-package dielectric barrier discharge plasma environment. (February 2016) - Pankaj, S.K.; Kelly, Caroline A.; Bueno-Ferrer, C.; Kerry, Joe P.; Papkovsky, Dmitri B.; Bourke, Paula; Cullen, P.J.
Abstract: Dielectric barrier discharge plasma treatment of two different types of phosphorescent oxygen sensors under different in-package gas mixture has been studied. Commercial Optech™-O2 platinum and microporous polypropylene (PP) membrane sensors impregnated with platinum benzoporphyrin (PtBP) dye were found effective for oxygen sensing when DBD plasma treated under modified atmospheric conditions. When treated under DBD air plasma, PP sensors were largely degraded and found incompatible with the plasma processing. Although some changes in the lifetime signals were observed after air plasma treatment, Optech™-O2 platinum sensors were found effective as oxygen sensors. This study indicates that in-package gas composition of food products plays an important role in selection of right intelligent optochemical sensors for plasma processing. Industrial Relevance: In-package cold plasma processing is emerging as a novel and innovative approach for the decontamination of food products with significant potential for commercial application. This paper studies the compatibility of phosphorescent oxygen sensors with this technology. This study demonstrates that the package gas composition has huge impact on the accuracy and usability of sensors. The work described in this research is relevant to all food industries which uses intelligent sensors for monitoring gas composition. Highlights: Compatibility of phosphorescent oxygen sensors were evaluated with in-package DBD cold plasma Under atmospheric air packaging, PP PtBP sensors were largely degraded. Re-calibration was required for Optech sensors under atmospheric air packaging. Under modified atmosphere packaging (no oxygen), both sensors were found effective.